2017
DOI: 10.1177/1468087417697759
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cavitation in common-rail diesel nozzles on the mixing process

Abstract: A study to experimentally analyze the effect of cavitation on the mixing process in diesel nozzles was carried out. The mixing process was studied through the spray cone angle. It was characterized in two different scenarios: with the liquid length (nearly realistic conditions, i.e. evaporative but non-reactive spray) and the heat release fraction (fully realistic conditions, i.e. evaporative and reactive spray). In both studied scenarios the increase of spray cone angle caused by the cavitation phenomenon, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Payri et al [12] investigated the internal flow in a transparent nozzle under cavitating conditions using an optical experimental system with a charge-coupled device (CCD) camera, and the results showed that the cavitation occurs before the mass flow collapse that takes place once the cavitation is fully developed through the whole orifice. Lopez et al [13] experimentally analyzed the effect of cavitation on the mixing process in nozzles and stated that the increment of the spray cone angle caused by the cavitation leads to a better mixing process. An optical experiment was carried out by He et al [14], and the bubble "suction" from orifice exit at the end of injection and the bubble "discharge" at the initial stage of the next injection were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Payri et al [12] investigated the internal flow in a transparent nozzle under cavitating conditions using an optical experimental system with a charge-coupled device (CCD) camera, and the results showed that the cavitation occurs before the mass flow collapse that takes place once the cavitation is fully developed through the whole orifice. Lopez et al [13] experimentally analyzed the effect of cavitation on the mixing process in nozzles and stated that the increment of the spray cone angle caused by the cavitation leads to a better mixing process. An optical experiment was carried out by He et al [14], and the bubble "suction" from orifice exit at the end of injection and the bubble "discharge" at the initial stage of the next injection were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many researchers have carried out a lot of research work around the structural parameters of electronic fuel injector. [12][13][14][15][16][17][18][19][20] These studies focus on the nozzle area. The effect of nozzle hole arrangements and structural parameters on the performance of the electronic fuel injector is discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The cone angle can be defined as the angle formed by two straight lines that start from the outlet hole at the nozzle and they are tangent to the spray contour. If the cone angle is greater, the air engulfing and mixing processes are better [16,19,20].…”
Section: Introductionmentioning
confidence: 99%